A gridRPC-based environment for grid computing - Ho, Quoc Thuan (2008)
This project aimed to develop an effective and efficient GridRPC-based environment for multiple clusters of computers distributed on the Grid. It contains programming and execution environments for GridRPC applications. The programming environment allows users to deploy GridRPC services and develop GridRPC applications to consume the existing services. In order to make the Grid transparent to the users, the GridRPC execution environment is equipped with many mechanisms for resource discovery, resource selection, request scheduling and dispatching. Especially, composite services and request bundling mechanisms are introduced and examined together with the aids of multithreaded programming techniques. They are useful to improve performance for embarrassingly parallel applications.